Time, Landscape and Burials. 1. Megalithic Rites of Ancient Peasant Societies in Central and Southern Portugal: an Intitial Overview. - Gonçalves, Victor S. (1999)
The author presents some questions about the big "half-orange" (the tumulus of classiccal passage graves) and about 'what lies under the peel' (the megalithic rituals). What are the meanings for the structure and for the type of burials? What is the significance for the number and nature of votive and ideotechnic artefacts? The decorated schist plaques are also discussed. Some monuments excavated by the author are specially referred: Penedos de S. Miguel (Crato), Olivald a Pega 2 (Reguengos de Monsaraz), Pedras Altas and Curral da Castelhana ( at the 'Alto Algarve Oriental'), Nevertheless, a particular attention is given to a key monument, Poço da GAteira 1 (Reguengos de Monsaraz).